2022
DOI: 10.3389/fpsyg.2022.919993
|View full text |Cite
|
Sign up to set email alerts
|

Tough Love: Impact of High-Performance Work System on Employee Innovation Behavior

Abstract: Based on the social exchange theory, this paper discusses the impact of high-performance work system (HPWS) on employee innovation behavior, constructs the mediating model of challenge stress and the moderated mediation model, and explores the influence mechanism of HPWS on employee innovation behavior under the management mode of combining strictness and love formed by “strictness” under the effect of challenge stress and “love” given by perceived organizational support. Through hierarchical regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The dominating assumption is that HPWS increases job demands ( Han et al, 2020 ). More specifically, we need an explanation for why the main effects of HPWS on job demands/stress is sometimes negative (e.g., Kloutsiniotis and Mihail, 2020 ; the present study) and sometimes positive ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ). One explanation may be omitted leadership variables, either in terms of their main effects (as in the present study) or as moderating substitutes (e.g., Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The dominating assumption is that HPWS increases job demands ( Han et al, 2020 ). More specifically, we need an explanation for why the main effects of HPWS on job demands/stress is sometimes negative (e.g., Kloutsiniotis and Mihail, 2020 ; the present study) and sometimes positive ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ). One explanation may be omitted leadership variables, either in terms of their main effects (as in the present study) or as moderating substitutes (e.g., Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…The mechanism of the latter remained unidentified in the present study. Together this emerging evidence calls into question the robustness and generalizability of theorizing ( Han et al, 2020 ) and empirical research that has found HPWS directly and positively related to work intensification ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ; see also Ehrnrooth and Bjorkman, 2012 ). Specifically, the change in the relationship between HPWS and job demands when accounting for TL in the present study was significant enough to shed some more doubt on the received view of the nature of this relationship (more on this in the next section).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These practices can improve employee engagement and motivation, which can lead to a greater commitment to organisational goals, including the development and implementation of digital innovations [20]. This enables employees to stay current with emerging technologies and fashions while also building the skills needed for digital innovation [24]. The application of digital technologies and business models that improve sustainability within the circular economy is made possible by digital innovation, which is inspired by HPWS [20].…”
Section: Hpws and Digital Innovationmentioning
confidence: 99%
“…Employee involvement and empowerment are key components of HPWS practices, which can boost innovation, knowledge exchange, and experimentation [25]. Therefore, HPWS practices place a strong emphasis on providing staff with chances for ongoing learning and growth [24]. Employees are more likely to provide original solutions and concepts for digital innovation when they are given the opportunity to participate in decision-making processes and to voice their opinions [26].…”
Section: Hpws and Digital Innovationmentioning
confidence: 99%